Elucidating the physicochemical properties of stingless bee honey as cryoprotectant and thermoregulated constituents - Shahbuddin, Munira; Raja Alias, Raja A’isyah Syahirah; Shahbuddin, Dahlia; Ngah, Norhayati (Chemical and Natural Resources Engineering Journal, 2024)
Stingless bee honey had been studied for their unique properties and their potential in medical aspects. In this study, the physicochemical properties of the stingless bee honey of Heterotrigona itama and Geniotrigona thoracica were investigated for their potential as cryoprotectant. The water content of the stingless bee honey was determined through water removal process where G. thoracica and H. itama contained 26.8% and 29.68% of water, respectively. The freezing point and properties of the stingless bee honey under different temperatures between 0?C, -20?C and -80?C were studied and the results showed that G. thoracica stingless bee honey had a slower freezing rate compared to H .itama. Thawing experiment of the stingless bee honey was conducted at room temperature in order to find the rate of thawing for the stingless bee honey. It was found that the melting rate of H. itama was slower compared to G. thoracica. Image analysis was done in order to analyze the freezing and melting rate of the stingless bee honey from G. thoracica and H. itama. DSC analysis thermograms of pure G. thoracica and pure H. itama stingless bee honey showed that the Tg value for G. thoracica was 36.64?C and H. itama was 58.06?C, while the Tm value of G. thoracica was 122.33?C and H. itama was 153.27?C. Finally, the Tc value for G. thoracica was 89?C, while for H. itama, the value was 129.47?C. Our study has shown that these stingless bee honey contained high water content and low Tg value. Stingless bee honey’s amorphous solid physicochemistry merit for study and should be further elucidated for its potential in cells and macromolecules such as mRNA and DNA protection and preservation under low temperature and extreme conditions.